Developing of Bacterial Mutagenic Assay System for Detection of Environmental and Food MutagensV – Using Anticancer Drug Cyclophosphamide - Baghdad Science Journal (مجلة بغداد للعلوم, 2008)
G-system composed of three isolates G3 ( Bacillus),G12 ( Arthrobacter )and G27 ( Brevibacterium) was used to detect the mutagenicity of the anticancer drug, cyclophosphamide (CP) under conditions similar to that used for standard mutagen, Nitrosoguanidine (NTG). The CP effected the survival fraction of isolates after treatment for 15 mins using gradual increasing concentrations, but at less extent comparing to NTG. The mutagenic effect of CP was at higher level than that of NTG when using streptomycin as a genetic marker, but the situation was reversed when using rifampicin resistant as a report marker. The latter effect appeared upon recording the mutagen efficiency (ie., number of induced mutants/microgram of mutagen). Measuring the Relative mutability revealed that isolate G12 was highly mutable by both mutagens. The Relative mutational results showed also that isolate G12 is more sensitive, except when recording rifampicin resistance as a genetic marker, and this pattern was similar to NTG.